Nano-enhanced organic form stable PCMs for medium temperature solar thermal energy harvesting: Recent progresses, challenges, and opportunities - Paul, John; A. K., Pandey; Mishra, Yogeshwar Nath; Said, Zafar; Mishra, Yogendra Kumar; Ma, Zhenjun; Jacob, Jeeja; K., Kadirgama; M., Samykano; V. V., Tyagi (Elsevier, 2022)
Solar energy is an easily accessible and promising renewable energy source that could solve the current energy crisis. Thermal energy storage systems incorporating Phase Change Materials (PCMs) are widely preferred owing to their immense energy storage capacity. The thermal energy storage (TES) potential of PCMs has been deeply explored for a wide range of applications, but not limited to solar/electrothermal energy storage, waste heat recovery, energy savings in building, and thermal regulations. The inherent shortcomings like leakage during phase transition, poor thermal conductivity hamper their extensive usage. Nevertheless, it has been addressed by their shape stabilization with porous materials and dispersing highly conductive nanoparticles. This review article focuses on different synthesis methods for medium-temperature form stable composites and a special focus is given on their thermal performance. Following mathematical evaluators (enthalpy efficiency, crystallization factor, efficient energy per unit mass of PCM, and thermal conductivity enhancement/mass fraction of nanoparticles) are computed and used to evaluate the efficacy of Form stable Nano-enhanced PCMs (FSNePCMs). The variations in thermophysical properties along with the critical causes are condensed. The effects of porous support on the degree of supercooling, form stability & thermal cycling are briefed. Furthermore, the versatile potential applications of the form stable composites are detailed. Finally, the possible future directions associated with the development of FSNePCMs with high energy density are highlighted. This review delivers a systematic and in-depth insight into the progress of FSNePCMs considering synthesis routes, thermal performance, energy density, and thermal management.